Rancang Bangun Sistem Informasi Marketplace Berbasis Web Khusus Freelance Fotografer - Fernando; Jullend Gatc (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The development of technology and science is very rapid, thanks to technological developments that spread information about photography. Media in promoting photography services at this time are still few and there are no application devoted to Freelance Photographers. One solution to this problem is to create a marketplace application specifically for Freelance Photographers to be able to market photography services. On the other hand, this application can be utilized by people who are looking for photography services. Freelance Photographer's special marketplace application is built with the waterfall method with the PHP programming language and MySQL database. The purpose of building this marketplace application is to expand opportunities for Freelance Photographers to get work projects, as well as facilitate people who need documentation services in finding photographer services in accordance with their desires and the appropriate budget.